Investigating Junior High School Students Perceptions on the Use Of Textbook "When English Rings A Bell" for Learning English Reading Materials in the Classroom - Alfathi Finna Hari; Bambang Arya Wijaputra; Rizki Febri Andika Hudori (EFL Education Journal, 2023)
This research aimed to enhance the eighth grade junior high school students’ on the use of textbook for learning reading materials in the classroom. In this research, the researcher was not intended to establish and prove hypotheses but it was aimed to describe the students’ perceptions on the use of textbook for learning reading English materials in the classroom. The participants of this research were six students of the 8th-grade students at SMPN 2 Mojowarno. The design of this research was descriptive qualitative method. The research instrument of this research included the interview with two students were with the highest scores, two students were with the middle scores, and two students were with the lowest scores in English which were then analyzed thematically. The findings showed that the students’ perceptions were divided into five themes: students’ interest, textbook layout, students’ difficulties, students’ experiences, and students’ benefits